2004
DOI: 10.2166/wst.2004.0002
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen removal efficiency from UASB + BF effluent using conventional and UV post-treatment systems

Abstract: The aim of this study was to verify the efficiency of removal of microorganisms in effluents of a Wastewater Treatment Plant (WWTP) comprising an association of a UASB reactor followed by three submerged aerated biofilters (BAF) and one tertiary filter. The WWTP designed to treat domestic wastewater from a population of 1,000 inhabitants showed high removal efficiency for organic matter and suspended solids. Helminth eggs were also efficiently removed from the tertiary effluent and were found in the sludge fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 3 publications
0
7
0
2
Order By: Relevance
“…This effect has also been reported by other authors using UASB effluents and UV disinfection. 21 In facultative pond and duckweed pond effluents, Salmonella was completely inactivated in the absence of TiO 2 using both BLL and the solar simulator. This could be due to the low turbidity and low concentrations of organic and inorganic matter in these effluents, as well as the low initial bacterial concentrations.…”
Section: Bacterial Inactivation In Absence Of Tiomentioning
confidence: 98%
“…This effect has also been reported by other authors using UASB effluents and UV disinfection. 21 In facultative pond and duckweed pond effluents, Salmonella was completely inactivated in the absence of TiO 2 using both BLL and the solar simulator. This could be due to the low turbidity and low concentrations of organic and inorganic matter in these effluents, as well as the low initial bacterial concentrations.…”
Section: Bacterial Inactivation In Absence Of Tiomentioning
confidence: 98%
“…1.0 log 10 removal for Salmonella spp., 0.5 log 10 removal for Shigella spp., 1.0 log 10 removal for Vibrio spp in a UASB reactor (Pant and Mittal, 2007) 1.1 log 10 reduction of thermotolerant coliforms in UASB reactors (Oliveira and von Sperling, 2011) 1.0 log 10 reduction of thermotolerant coliforms in an ABR reactor (Lalbahadur et al, 2005) 0.3 log 10 removal of Cryptosporidium oocysts (Morsy et al 2007) 0.42 to 1.30 log 10 for UASBs (Keller et al, 2004;von Sperling et al, 2003;Yaya-Beas et al, 2015).…”
Section: Factors Contributing To Removalmentioning
confidence: 99%
“…Although the efficiency of the UASB-SABF system was satisfactory in terms of organic matter removal, the removal of the pathogenic microorganisms was very low. Keller et al (2004) investigated the combined UASB-SABF system followed by conventional and UV system to enhance the efficiency of the system to remove the pathogenic microorganisms. The results revealed that the 84% of COD (residual effluent COD of 78 mg/L), 86 % of BOD (residual effluent BOD of 26 mg/L) and 86% of TSS (residual effluent TSS of 23 mg/L) removal was achieved.…”
Section: Submerged Aerated Bio-filter (Sabf)mentioning
confidence: 99%